Changes in the lifestyle and feeding habits that could improve the planet and human health: the reproductive case - Gutiérrez, Alejandra María Gómez; Ramírez, Briana D. Gómez; Maya, Walter D. Cardona (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
There is a link between food systems, environment, and human health. According to the Food and Agriculture Organization of the United Nations-FAO, food production from animal and plant origin, using unsustainable agricultural practices with the excessive use of fertilizers, pesticides, fungicides, and herbicides have adverse effects on the environment and could contaminate water sources and even the soil.1 Also, the production of food from animal origin is one of those responsible for the emission of greenhouse gases, fresh water expenditure, and soil loss. Therefore, with the current food consumption and unsustainable human practices, the future of humanity will be uncertain.